The effect of titanium insert repairs on the static strength of CFRP coupons and joints. (15th December 2015) - Falconieri, Diletta; Franco, Francesco
Abstract: In engineering industry, the panels manufacturing implicates the risk of having defects or damages due to deviations in the assembly and machining processes. A hole's repair solution adopts the installation of titanium insert(s), avoiding the use of bigger fasteners. The fundamental requirement is to continue to guarantee high performances and efficiency of the jointed panels of the aircraft. Although this technique is diffused in metallic structures, its use is far from being completely understood in the case of composites (CFRP). In addition, differently from metals, the failure mechanisms of a composite joint are more complicated, since they vary with material properties, geometrical parameters and stress concentrations. For the above reasons, static tests are performed on different types of coupons and joints, manufactured from a carbon fiber/epoxy material and joined by countersunk fasteners. Coupons with nominal fasteners are taken as reference, while, in the remaining samples, selected holes are repaired using different inserting principles. All the tests are carried out until the final failure, in order to obtain results of the ultimate strength, especially related to the influence on the occurred failure mode(s). It is also highlighted that the assessment of the load transfer between the joint parts, and the stress distribution depend on the chosen inserting principle (countersunk/cylindrical and symmetrical/asymmetrical), on the size and on the location of repair inserts. Extensometers are used to measure relative displacements between the composite plates. Strain gauge measurements are performed on one family of coupons, in order to analyze the strain distribution in the area nearest to the hole in case of insert installed.